History as a critical theory. The intellectual history of Dominick LaCapra - Hervás, Alfonso Galindo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This article has two objectives. The main one is to show the conception of historiography as a critical theory in the work of Dominick LaCapra. The secondary is to expose the impolitical consequences of contemporary critical theory that underestimates attention to history. For that purpose, I frame the intellectual history of LaCapra in the context of the renewal of historiographical methodology and I show the relevance of the study of trauma in his conception of historical knowledge. After that, I show that the key that converts his concept of history into a critical theory is the idea that history should contribute to the elaboration of trauma and empowering for action, as well as the relationship between this idea and the link between experience and political identity. Then I expose LaCapra’s criticism to a contemporary trend of critical theory that renounces the elaboration of trauma. Finally, I propose three categories to identify and analyze this trend: historical difference, ethical turn and impoliticity.